2011
DOI: 10.1007/s00726-011-1150-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation exploration of unfolding and refolding of a ten-amino acid miniprotein

Abstract: Steered molecular dynamics simulations are performed to explore the unfolding and refolding processes of CLN025, a 10-residue beta-hairpin. In unfolding process, when CLN025 is pulled along the termini, the forceextension curve goes back and forth between negative and positive values not long after the beginning of simulation. That is so different from what happens in other peptides, where force is positive most of the time. The abnormal phenomenon indicates that electrostatic interaction between the charged t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 67 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…The lower black curve was obtained from a 5 μs-long folding simulation of the CLN025 peptide 10 . CLN025 is known to be a fast and stable β-hairpin folder 18 , and in agreement with these studies our trajectory contains more than ~50 folding/unfolding events (data not shown). On the other hand, the LytaA-derived peptide (upper magenta curve in Fig.2a) is a very slow and erratic folder, possibly due to the presence of significant energetic frustration in its folding landscape.…”
Section: The Methods Is Consistent With Other Established Algorithmssupporting
confidence: 91%
“…The lower black curve was obtained from a 5 μs-long folding simulation of the CLN025 peptide 10 . CLN025 is known to be a fast and stable β-hairpin folder 18 , and in agreement with these studies our trajectory contains more than ~50 folding/unfolding events (data not shown). On the other hand, the LytaA-derived peptide (upper magenta curve in Fig.2a) is a very slow and erratic folder, possibly due to the presence of significant energetic frustration in its folding landscape.…”
Section: The Methods Is Consistent With Other Established Algorithmssupporting
confidence: 91%
“…On the other hand, methanol (MeOH), as an ideal hydrogen-donating (protic) solvent, has been commonly used in the study of the effects of excited-state hydrogen bonding interactions on the photophysical properties of some molecular systems. [12][13][14][15][16][17] The significant strengthening of the intermolecular hydrogen bond in the hydrogen-bonded fluorenone (FN)-MeOH complex has been demonstrated to be responsible for the drastic quenching of the fluorescence emission of fluorenone in protic solvents by facilitating the internal conversion (IC). 12 Furthermore, the ultrafast intermolecular electron transfer (ET) reaction in the hydrogen-bonded oxazine 750 (OX750)-MeOH complex that is facilitated by strengthening of intermolecular hydrogen bonding in the excited states has been studied by Zhao et al 13 It has been demonstrated both theoretically and experimentally that the fluorescence quenching of the OX750 dye in protic solvents should be attributed to the solute-solvent intermolecular photoinduced electron transfer from protic alcohols to the OX750 chromophore, which is facilitated by the strengthening of the selected hydrogen bonds in the excited states.…”
Section: Introductionmentioning
confidence: 99%
“…13 Moreover, Liu et al 14 have found that the intermolecular hydrogen bond formed between 2-(4=-N,N-dimethylaminophenyl)imidazo [4,5-b]pyridine (DMAPIP) and MeOH molecules can induce the formation of the twisted intramolecular charge transfer (TICT) state for DMAPIP in MeOH solvent. 17 Recently, it has been demonstrated that the time-dependent density functional theory (TD-DFT) method can be used to effectively study the electronic transitions and excited-state properties of hydrogen-bonded complexes. [18][19][20][21][22][23][24][25][26][27][28] Therefore, to investigate the excited-state hydrogen bonding effects on the transfer properties of the hydrogen-bonded 3TPAN-MeOH complex, the geometric structures and electronic transition energies as well as corresponding oscillation strengths of the two low-lying electronically excited states S 1 and S 3 for both the 3TPAN monomer and the hydrogen-bonded 3TPAN-MeOH complex were calculated by DFT and TD-DFT methods, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Being widely recognized, the nature and law of the hydrogen bonding has become one of the contemporary research interests in chemical and biochemical areas. Important results on various properties of many hydrogen-bonded complexes have been obtained in a number of theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and experimental works, [20][21][22][23][24][25] which include their geometrical structures, electronic spectras, electrostatic potential (ESP maps), the energy changes of the intermolecular hydrogen bond upon electronic excitation, the self-assembly issues, [18,19] and its influence on the photophysical and photochemical properties of the hydrogen-bonded molecules. Specifically, intermolecular hydrogen bonds have been found to have significant influences on the photophysical properties of compounds including heterocyclic aromatic [26] and carbonyl groups.…”
Section: Introductionmentioning
confidence: 99%